Steve Jobs [videorecording (DVD)] : one last thing - Challis, Jonathan; Challis, Jonathan; Coffey, John; Coffey, John; Crook, Susan; Crook, Susan; Lynch, Ian; Lynch, Ian; Jobs, Steve, 1955-2011; Goritsas, Demetri (PBS Distribution, 2011)
This documentary looks not only at how his talent, style and imagination have shaped all of our lives, but also at the influences that shaped and molded the man himself. Through interviews with the people who worked closely with him or chronicled his life, we gain unique insight into what made him tick. In a never before broadcast, exclusive interview, Steve Jobs expounds his own philosophy of life, and offers advice to us all on changing our own lives.